All in a drop : how Antony van Leeuwenhoek discovered an invisible world - Alexander, Lori (Houghton Mifflin Harcourt, 2019)
"For fans of the "Who Was" series, this lively, accessible, and full-color chapter book biography shows how a self-taught scientist was the first to observe the microbial life in and around us. By building his own microscope, Antony van Leeuwenhoek advanced humanity's understanding of our oft-invisible world around us."--